Molluscs in archaeological contexts of atlantic coast of Tierra del Fuego: prehistoric consumption and implications of current distribution - Santiago, Fernando; Gordillo, Sandra; Salemme, Mónica (Revista Chilena de Antropología, 2015)
This paper analyzes archaeomalacological data from three archaeological sites –two shell middens and an open air site – located northern Río Grande city, in the Fuegian steppe and dated by the middle and late Holocene. This data is compared with the malacofauna coming from other archaeological sites of northern Tierra del Fuego and with the mollusks living in the region today. Six sampling were done nearby the best known archaeological sites with the aim of checking the present distribution of the species. Some interpretations on distribution and palaeoecology of several mollusk species as well as its potential as economic resource for hunter gatherers of Tierra del Fuego are offered.